Amplitude spectral area of ventricular fibrillation can discriminate survival of patients with out-of-hospital cardiac arrest - Gentile, Francesca Romana; Wik, Lars; Isasi, Iraia; Baldi, Enrico; Aramendi, Elisabete; Steen-Hansen, Jon Erik; Fasolino, Alessandro; Compagnoni, Sara; Contri, Enrico; Palo, Alessandra; Primi, Roberto; Bendotti, Sara; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Evidence of the association between AMplitude Spectral Area (AMSA) of ventricular fibrillation and outcome after Out-of-Hospital Cardiac Arrest (OHCA) is limited to short-term follow-up. We assessed if AMSA could stratify the risk of death or poor neurological outcome at 30-days and one year after OHCA in patients with initial shockable or non-shockable rhythm. Methods: This is a multicentre retrospective study of prospectively collected data in two European Utstein-based OHCA registries. We included all the OHCAs with at least one manual defibrillation. AMSA values were calculated after data extraction from the monitors/defibrillators used in the field by using a 2-second-pre-shock electrocardiogram interval. The first AMSA value detected, the maximum, the average and the minimum values were computed, and their outcome prediction accuracy was compared. Multivariable Cox regression models were run for both 30-day and one-year death or poor neurological outcome. Neurological cerebral performance category (CPC) 1-2 was considered as good neurological outcome. Results. Out of the 578 patients included, 494 (85%) died and 10 (2%) had a poor neurological outcome at 30 days. All the AMSA values considered (first value, maximum, average and minimum) were significantly higher in survivors with good neurological outcome at 30 days. The average AMSA showed the highest Area Under the ROC Curve [0.778, (95%CI: 0.7-0.8), p<0.001]. After correction for confounders, the highest tertiles of average AMSA (T3 and T2) were significantly associated with a lower risk of death or poor neurological outcome compared to T1 both at 30-days [T2: HR 0.6 (95%CI 0.4-0.9), p =0.01; T3: HR 0.6 (95%CI 0.4-0.9), p=0.02] and at one year [T2: HR 0.6 (95%CI 0.4-0.9), p=0.01; T3: HR 0.6 (95%CI 0.4-0.9), p=0.01]. Among survivors at 30-days, higher AMSA was associated with a lower risk of mortality or poor neurological outcome at one year [T3: HR 0.03 (95%CI 0-0.3), p=0.02]. Discussion. Lower AMSA values were significantly and independently associated with the risk of death or poor neurological outcome at 30-days and at one year in OHCA patients with either initial shockable rhythm or conversion rhythm from non-shockable to shockable. The average AMSA value had the strongest association with prognosis.